Influence of overstory density on understory light, soil moisture, and survival of two underplanted oak species in a Mediterranean montane Scots pine forest - Rodriguez Calcerrada, J.=700 1 Mutke, S.; Alonso, J.; Gil, L.
(En, Es)
ilus., 43 ref.
Keywords: QUERCUS PETRAEA; QUERCUS PYRENAICA; ACLAREO; PLANTACION; CUBIERTA DE COPAS; SEQUIA; ESPAÑA